1989
DOI: 10.1002/cne.902860405
|View full text |Cite
|
Sign up to set email alerts
|

Transient GABA immunoreactivity in cranial nerves of the chick embryo

Abstract: The distribution and time course of gamma-aminobutyric acid (GABA) immunoreactivity was investigated in the cranium of the chick embryo from 2 to 16 days of incubation (E2-16). A fraction of nerve fibers transiently stains GABA-positive in all cranial motor nerves and in the vestibular nerve. Cranial motor nerves stain GABA-positive from E4 to E11, including neuromuscular junctions at E8-11; labeled fibers are most frequent in the motor trigeminal root (E6-9.5). Substantial GABA staining is present from E4 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 81 publications
4
9
0
Order By: Relevance
“…Previous studies using traditional retrograde labeling methods have reported that SON neurons are resistant to labeling (Correia et al, 1982;von Bartheld and Rubel, 1989). Our initial experiments using iontophoresis or pressure injections of fluorescently tagged dextrans confirmed these difficulties.…”
Section: In Vitro Electroporationsupporting
confidence: 77%
“…Previous studies using traditional retrograde labeling methods have reported that SON neurons are resistant to labeling (Correia et al, 1982;von Bartheld and Rubel, 1989). Our initial experiments using iontophoresis or pressure injections of fluorescently tagged dextrans confirmed these difficulties.…”
Section: In Vitro Electroporationsupporting
confidence: 77%
“…In mice, it has been shown that GABA influences the development of the GnRH system [Fueshko et al, 1998;Bless et al, 2000]. GABA is transiently expressed during development [von Bartheld and Rubel, 1989;Barale et al, 1996;Tobet et al, 1996a], and in explants from embryonic mice, synaptic input from GABAergic cells caused spontaneous activity in GnRH neurons [Kusano et al, 1995]. The published results in other species suggest that GnRH neurons possess GABA receptors and are responsive to GABA early in development.…”
Section: Discussionmentioning
confidence: 49%
“…Whilst the role of GABA in undifferentiated cells remains unknown, some lines of evidence suggest that GABA has neurotrophic effects on developing cranial nerves or their target tissue (von Bartheld et al, 1989). In fact, it has been shown that some of the GABAergic interneurons of the OB are derived from the subventricular zone (Betarbet et al, 1996).…”
Section: Olfactory Bulb-like Structures In the Sey Neu Mutantmentioning
confidence: 99%